#TITLE_ALTERNATIVE# - HIDAYATUL KHAIR(NIM: 15108098); pembimbing: Dr. rer. nat. Wiwin Windupranata, ST.; Dr. rer. nat.
Indonesia is an archipelago that holds great potential for welfare of the society, especially in the ocean. However, this great potential has not been used optimally. Optimal utilization can be done with the use of controlled technology. In the application of technology, needed research about phenomena in the ocean. One of the phenomena that occur in the ocean is tidal. The purpose of this thesis is to create a map of the type and range ocean tidal in Indonesia. Mapping types and tidal range using data from satellite altimetry. Altimetry satellites measure sea level on a regular basis by calculating the tidal components to obtain the global tide models TPXO 7.1. Models extract the data to get value of amplitude. Extraction results are then displayed in ArcGIS. Type of tides in Indonesia is divided by the formation of wave patterns into four types, that is diurnal, semidiurnal, mix tide prevailing diurnal, and mix tide prevailing semidiurnal. From the results of mapping types tide in Indonesia, which is predominantly a mix tide prevailing semidiurnal while tidal range in Indonesia has a value between 0.1 m and 2.9 m for the use of four components and between 0.5 m to 6.9 m for the using 11 tidal components.